2019
DOI: 10.1002/ajh.25579
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous extramedullary relapse in multiple myeloma ‐ a multicenter retrospective study in 127 patients

Abstract: The current study assesses the characteristics and outcomes of multiple myeloma (MM) patients, treated with novel agents for hematogenous extramedullary (HEMM) relapse. Consecutive patients diagnosed with HEMM between 2010-2018 were included. Patients' characteristics at diagnosis and at HEMM presentation, response to treatment, survival and factors predicting survival were recorded and analyzed. A group of 127 patients, all diagnosed with HEMM by imaging (87.3%) and/or biopsy (79%), were included. Of those, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
2
14
0
2
Order By: Relevance
“…At the beginning, patients with EMD may respond to the initial treatment of bortezomib and other new drugs, but they may not avoid the development of escape of apoptosis and therapeutic resistance. Furthermore, they tend to acquire a more aggressive disease in later stages ( 24 , 25 ), which is consistent with the clinical treatment response observed in the real world.…”
Section: Discussionsupporting
confidence: 83%
“…At the beginning, patients with EMD may respond to the initial treatment of bortezomib and other new drugs, but they may not avoid the development of escape of apoptosis and therapeutic resistance. Furthermore, they tend to acquire a more aggressive disease in later stages ( 24 , 25 ), which is consistent with the clinical treatment response observed in the real world.…”
Section: Discussionsupporting
confidence: 83%
“…In our own series, the median survival of 29 patients with EMD disease at diagnosis was significantly shorter than that of 191 patients with PS plasmacytomas (1·8 vs. 3·5 years) 33 . A multicentre study of 127 patients with EMD disease also showed dismal outcome 78 . The prognosis is particularly poor in patients with CNS involvement who have a median survival of <3 months, 38,39 and even when novel agents are used outcomes to date have been dismal 41,79,80 .…”
Section: Prognosismentioning
confidence: 62%
“…The presence of extramedullary myeloma, namely EMM, usually portends inferior outcomes for MM patients, even in the era of novel agents and stem cell transplantation (2,(29)(30)(31). Driven by multiple genetic and microenvironmental mechanisms, certain MM subclones are predisposed to survive outside the BM niche (5,32).…”
Section: Discussionmentioning
confidence: 99%